Penguatan Moderasi Beragama di Tingkat Desa melalui Pendekatan Partisipatif KKN: Studi di Desa Gemuhblanten - Latif, Helmi Abdul; Husni, Muhammad Arfi; Nisak, Salisa Amanin; Wahyuningsih, Nurul Aisyah; Nafi', Imam Ajyain; Kamelia, Aisyah; Azizah, Lutfiyah; Sholahudin, Muhammad Azmi; Salsabila, Kharisma; Ubaidillah, Huda; Safitri, Ifa; Saputra, Irfan Maulana; Hafshoh, Zanuba Arifah; Efendi, Samsul (LPPM Sekolah Tinggi Islam Kendal, 2026)
Gemuhblanten Village is an area that has religious diversity in its community life. These social conditions require mutual respect and tolerance between religious communities in order to create a harmonious social life. This community service activity aims to find out and describe the patterns of the Gemuhblanten Village community in facing the acceptance of religious moderation in everyday life. The series of activities began with field observations, then continued with an interview process with village heads and community leaders, as well as documentation as supporting data. The results of the activity show that the people of Gemuhblanten Village are able to apply the values of religious moderation through harmonious social interaction, mutual respect between religious believers, acceptance of the existence of different places of worship, as well as cross-religious participation in various social and religious activities. This activity has a positive impact in maintaining religious harmony at the village level and is hoped to become an example of implementing religious moderation in other areas.